Nasionalisme Kulit Putih: Ernest Douwes Dekker Malaikat Pemberani - Samingan (Program Studi Pendidikan Ekonomi, Universitas Flores, 2017)
The problem in this research is how the form of nationalism of Indo Ernest Douwes Dekker to fight for equality between all layers with the Europeans. Through the tortuous struggle undergo various disposal has spawned a sense of nationalism as the basis of pinjakan for Indonesia Merdeka. The purpose of the study was to find out how Ernest Douwes Dekker's nationalism fought to achieve equality between European white people and indigenous peoples and Indo. The method used in this study using the method of History (historical method). The steps used in this study, which is first is to collect the source (heuristic), the second is the source or verification criticism, the third step is the interpretation, the fourth step historiografi reconstruction (writing) history. The results show that: Douwes Dekker is a descendant of the Netherlands. His concern for the colonial nation's oppression of the Natives tapped his conscience to fight for the Indo (The Dutch) Natives of all discrimination. The real step taken by Douwes Dekker to voice his aspirations is to establish a political party or known as Indische Partij. Tjipto is known to oppose a deeply rooted feudal system, while Soewardi who is a member of the Pakualaman kingdom rejects cultural subordination under Western imperialism. The three of them combined into a triad to oppose colonialism through its political party. The twists and turns of his struggle so that all three of them are dumped. The result of this triad effort has led to the roots of nationalism to fight for Indonesian independence.